From Molar Pregnancy, Thyrotoxicosis, to Pulmonary Hypertension: A Case Report - Saputra, Rudi; Azra, Dieni; Aswad, Fidya Mayastri; Nurtanio, Setyawan (Fakultas Kedokteran Universitas Andalas, 2024)
Background: Molar pregnancy is a benign condition with the dominant symptom being dark brown to bright red bleeding from the vagina. This disease can induce hyperthyroidism and result in pulmonary hypertension. This case report describes a patient who had molar pregnancy with thyrotoxicosis and pulmonary hypertension.Case: A 30-year-old woman presented with complaints of lower abdominal pain for the last month. The patient feels that her stomach has enlarged in the last 3 months. Other complaints include bleeding and observed bubbles from the birth canal, shortness of breath, and chest pain. The serum cobas Î²-hCG level of 7954.00 mIU/mL. On abdominal ultrasound examination, vesicles formed a honeycomb appearance, measuring 7.4 cmÃ—5.3 cm. Hematologic laboratory tests revealed low TSH levels (<0.01 Î¼IU/mL), T3 levels of 2.35 ng/ml, and FT4 levels of 2.62 ng/dL. The results of the echocardiography examination showed there is a high probability of pulmonary hypertension.Conclusion: Molar pregnancy can exacerbate thyrotoxicosis through hCG activity. Smoking and breastfeeding also have similar effects. Consequently, increased thyroid hormone levels can worsen or cause pulmonary hypertension.